2020
DOI: 10.3390/cancers12061563
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of MHC-I on Tumor Cells by Fhit Transfection Promotes Immune Rejection and Acts as an Individualized Immunotherapeutic Vaccine

Abstract: The capacity of cytotoxic-T lymphocytes to recognize and destroy tumor cells depends on the surface expression by tumor cells of MHC class I molecules loaded with tumor antigen peptides. Loss of MHC-I expression is the most frequent mechanism by which tumor cells evade the immune response. The restoration of MHC-I expression in cancer cells is crucial to enhance their immune destruction, especially in response to cancer immunotherapy. Using mouse models, we recovered MHC-I expression in the MHC-I negative tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…We also observed that late Panobinostat but not early Panobinostat led to a significant loss in DNA methylation at a loci in the gene Fragile Histidine Triad Diadenosine Triphosphtatase (FHIT). Recent work has shown that FHIT gene transfection in mice restores MHC-I expression, and Panobinostat has been shown to augment the expression of MHC genes and HIV antigen processing and presentation [57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that late Panobinostat but not early Panobinostat led to a significant loss in DNA methylation at a loci in the gene Fragile Histidine Triad Diadenosine Triphosphtatase (FHIT). Recent work has shown that FHIT gene transfection in mice restores MHC-I expression, and Panobinostat has been shown to augment the expression of MHC genes and HIV antigen processing and presentation [57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, loss of Fhit expression in human breast tumors is associated with loss of HLA-I molecules. 68 The non-classical HLA-I molecules (notably HLA-E and HLA-G) have slightly different regulatory sequences, providing the opportunity for differential expression of classical and non-classical HLA genes through transcription factor variation (figure 2B). Both regulatory modules mentioned above can be identified in the HLA-E and HLA-F promoter regions, however in HLA-E the κB1 and κB2 and ISRE sites are different from the classical genes meaning that HLA-E is thought to be not induced by NF-κB, although an upstream GAS site provides strong inducibility by IFN-γ.…”
Section: Transcriptional Silencingmentioning
confidence: 99%
“…Re-expression of Fhit restored the MHC-I expression in this clone. The same group recently reported that in MHC-I negative breast cancers the loss of NLRC5 is less frequent than the loss of FHIT, and that FHIT could be used to restore MHC-I expression [ 254 ]. As FHIT does not upregulate NLRC5 expression, the molecular pathways by which FHIT upregulates MHC-I remains to be determined [ 254 ].…”
Section: Restoring Mhc-i Expression In Cancersmentioning
confidence: 99%